Biological control of Botrytis cinerea in the postharvest of strawberry fruits by Muscodor sp. - Oliveira, Larissa Maia de (2017)
Gray mold, caused by Botrytis cinerea, is one of the most important post-harvest diseases in strawberry fruits. This pathogen is responsible for great losses in packaged strawberries. Latent spores may be present on the surface of fruits harvested in the field, but symptoms appear only in post-harvest. To control the disease in the field, fungicide applications begin at flowering. Strawberry is one of the fruits with the highest amounts of pesticide residues. Currently, there are no fungicides registered for applications in post-harvest. Thus, the search for biological control agents has been the focus of several research groups. Fungi that produce volatile organic compounds (VOCs) were shown to control phytopathogens in different systems. The objective of this study were to isolate, select and develop a biological product based on VOCs production fungus with the capacity to control B. cinerea in packaged strawberries. Among the endophytic fungi isolated from different host plants and tested against B. cinerea, isolate FTB01 obtained from leaves of the parasitic plant Struthanthus sp. has been shown to completely inhibit mycelial growth of B. cinerea by the production of VOCs. Several substrates were tested to optimize the growth and production of VOCs and millet grains were ideal because of its ease to find and its relative low cost. Experiments employing grinded millet grains mixed with water-agar showed that the capacity of isolate FTB01 to control B. cinerea varied according to the temperature and the time of incubation of the antagonistic fungus in relation to the pathogen. However, when whole millet grains colonized by isolate FTB01 were used to fill sachets and those employed against B. cinerea, complete inhibition of the pathogen was observed regardless of the temperature of incubation. Ten VOCs were identified in the headspace of isolate FTB01 grown on millet grains by gas chromatography coupled to mass spectrometry. Isolate FTB01 was identified as a species in the genus Muscodor on the basis of the lack of reproductive structures and sequence analysis of ITS region of the ribosomal DNA. Based on the results, Muscodor sp. FTB01 is a potential biological agent to control B. cinerea in packaged strawberries.